DETERMINATION OF THE LIMITING STATE OF TENSION BOLT OF ROTOR TURBINE ENGINES - V. S. Dvoeglazov; D. Yu. Kiselev; Yu. V. Kiselev (Научный вестник МГТУ ГА, 2016)
The article presents a method of screening caps crew of engine rotors. In the absence of data on the amount of elon-gation for coupling bolts after a few repairs, a method of fault detection through caps crew on the magnitude of its reduc-tion.